2017
DOI: 10.1103/physrevb.95.085308
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic magnetotransport in Dirac-Weyl magnetic junctions

Abstract: We theoretically study the anisotropic magnetotransport in Dirac-Weyl magnetic junctions where a doped ferromagnetic Weyl semimetal is sandwiched between doped Dirac semimetals. We calculate the conductance using the Landauer formula and find that the system exhibits extraordinarily large anisotropic magnetoresistance (AMR). The AMR depends on the ratio of the Fermi energy and the strength of the exchange interaction. The origin of the AMR is the shift of the Fermi surface in the Weyl semimetal and the mechani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The bulk Hall effect with a large Hall angle can be achieved in magnetic Weyl semimetals (WSMs). The magnetic WSM [6][7][8][19][20][21][22][23][24] is a time-reversal-broken topological state and is one of the promising systems for next-generation spintronics devices due to its fancy transport properties (e.g., huge longitudinal magnetoresistance effects [25][26][27]). The magnetic WSM state is proposed in magnetic kagome layered materials (Fe 3 Sn 2 [28,29], Co 3 Sn 2 S 2 [30][31][32][33][34][35][36], and Mn 3 Sn [37][38][39]), and Heusler compounds (Ti 2 MnAl [40], Co 2 MnGa [41,42], and Co 2 MnAl [43]).…”
Section: Hall Magnetoresistancementioning
confidence: 99%
“…The bulk Hall effect with a large Hall angle can be achieved in magnetic Weyl semimetals (WSMs). The magnetic WSM [6][7][8][19][20][21][22][23][24] is a time-reversal-broken topological state and is one of the promising systems for next-generation spintronics devices due to its fancy transport properties (e.g., huge longitudinal magnetoresistance effects [25][26][27]). The magnetic WSM state is proposed in magnetic kagome layered materials (Fe 3 Sn 2 [28,29], Co 3 Sn 2 S 2 [30][31][32][33][34][35][36], and Mn 3 Sn [37][38][39]), and Heusler compounds (Ti 2 MnAl [40], Co 2 MnGa [41,42], and Co 2 MnAl [43]).…”
Section: Hall Magnetoresistancementioning
confidence: 99%
“…The system we will study is schematically shown in Figure 1, which is often called the Dirac–Weyl magnetic junction . The arrows denote the direction of electrons and L is the length of the ferromagnetic Weyl semimetal, which is sandwiched between two Dirac semimetals.…”
Section: In a Dirac–weyl Magnetic Junctionmentioning
confidence: 99%
“…This attractive field begins with the discovery of topological insulators (TIs) with various peculiar physical phenomena, such as the quantum spin Hall effect and the quantum anomalous Hall effect . The realizations of Dirac, Weyl, and nodal line semimetals give us the chance to paint a portrait on a much larger canvas . Particularly, a Dirac semimetal can exhibit double degeneration of the pseudorelativistic linear dispersions with time‐reversal and spatial‐inversion symmetries, while Weyl semimetals provide the gapless linear dispersions with broken time‐reversal or spatial‐inversion symmetries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was seen both analytically and numerically that a magnetic domain wall in a Weyl semimetal gives rise to a large domain wall magnetoresistance, due to the mismatch of the electron helicity beyond the domain wall. [160,161] One of the peculiar features of magnetic domain walls in Weyl semimetals is the emergence of 1D zero modes localized at the domain wall. [130,131] These zero modes can be regarded as the remnant of the surface Fermi arc of Weyl semimetal.…”
Section: Example: Magnetic Domain Wallsmentioning
confidence: 99%